Analysis of genetic diversity in two different shell colors of the giant triton snail (Charonia tritonis) based on mitochondrial COI sequences - Cen, Xitong; Zhang, Gege; Liu, Huiru; Yao, Gaoyou; Xiong, Panpan; He, Maoxian; Liu, Wenguang (Frontiers in Marine Science, 2023)
The giant triton snail (Chanoria tritonis) is widely distributed in tropical coral reefs in the Indo-West Pacific. Its distribution areas in China include the Penghu Islands, Hengchun Peninsula, and Xisha Islands. In this study, we conducted sequence analysis of the mitochondrial cytochrome oxidase (COI) gene to assess the affinity of C. tritonis with two different shell colors. The mitochondrial DNA COI sequences of 28 C. tritonis were all 603 base pairs in length, and seven haplotypes were subsequently detected from the samples. We constructed phylogenetic evolutionary trees using the neighbor joining, Maximum likelihood (ML), and unweighted pair-group method with arithmetic means (UPGMA) methods, constructed haplotype network diagrams, performed Tajima’s D and Fu’s neutrality tests, and calculated a gene flow of 11.78 and a genetic differentiation coefficient of 0.02078. Our results indicated that the population size remained relatively stable and the genetic differentiation between the two different shell colors was small. The mitochondrial COI gene fragments of the two different shell colors were sequenced and analyzed to accumulate information about the population genetics of C. tritonis and to provide a scientific basis for the conservation of its species resources.